STUDYING SOURCES REGARDING CENTRAL ASIA IN EUROPE (XIX - EARLY XX CENTURIES) - Rasulova Durdona Bakhronovna (Scholar Express Journal, 2021)
This article provides a comprehensive analysis of the study of the sources of nature, geography and culture of Central Asia in Europe. It also reveals the role of these sources in the study of European scientific schools and the establishment of the "Central Asian Studies" on its basis.
Keywords: Central Asia, Oriental Studies, Sources, Natural Sciences, Culture, Science and Education